A novel therapy for colitis utilizing PPAR-γ ligands to inhibit the epithelial inflammatory response - Su, Chinyu G. (American Society for Clinical Investigation, 1999)
Peroxisome proliferator-activated receptor γ (PPAR-γ), a member of the nuclear hormone receptor superfamily originally shown to play a critical role in adipocyte differentiation and glucose homeostasis, has recently been implicated as a regulator of cellular proliferation and inflammatory responses. Colonic epithelial cells, which express high levels of PPAR-γ protein, have the ability to produce inflammatory cytokines that may play a role in inflammatory bowel disease (IBD). We report here that PPAR-γ ligands dramatically attenuate cytokine gene expression in colon cancer cell lines by inhibiting the activation of nuclear factor-κB via an IκB-α–dependent mechanism. Moreover, thiazolidinedione ligands for PPAR-γ markedly reduce colonic inflammation in a mouse model of IBD. These results suggest that colonic PPAR-γ may be a therapeutic target in humans suffering from IBD. J. Clin. Invest. 104:383-389(1999).